Imbalance of Autophagy and Apoptosis Induced by Oxidative Stress May Be Involved in Thyroid Damage Caused by Sleep Deprivation in Rats. (11th September 2021) - Li, Yongmei; Zhang, Wei; Liu, Mengqi; Zhang, Qiuping; Lin, Zijie; Jia, Miao; Liu, Dan; Lin, Laixiang
Abstract : Many studies have shown that sleep deprivation can affect a wide range of tissues and organs, and most of these effects are related to oxidative stress. Oxidative stress can cause functional and morphological changes in cells, which are closely related to autophagy and apoptosis. In this study, we examined changes in thyroid morphology and function, oxidative stress, autophagy, and apoptosis in rats after sleep deprivation. Thyroid hormones, thyroid-stimulating hormone, functional substances required for the synthesis of thyroid hormones, and thyroid morphological observations were used to evaluate the changes and impairment of thyroid function. Methane dicarboxylic aldehyde and total antioxidant capacity were measured to assess oxidative stress in the thyroid. To evaluate the balance of autophagy and apoptosis, the expression of autophagy- and apoptosis-related proteins was examined by western blotting, and apoptotic cells were labeled with TUNEL staining. The body weight of rats in the sleep deprivation group decreased, but the relative weight of the thyroid gland increased. Sleep deprivation led to morphological changes in the thyroid. The levels of thyroid hormones and thyroid-stimulating hormone increased after sleep deprivation. Total antioxidant capacity decreased, and methane dicarboxylic aldehyde levels increased in the thyroid in the sleep deprivation group. Analysis of autophagy- and apoptosis-related proteins indicated that the microtubule-associated protein 1 light chain 3 beta- (LC3B-) and LC3A-II/I ratio and Beclin 1 levels significantly decreased in the sleep deprivation group and P62 levels significantly increased. The number of apoptotic cells in the thyroid gland of sleep-deprived rats increased significantly. Taken together, these results indicate that sleep deprivation can lead to oxidative stress in the thyroid and ultimately cause thyroid damage, which may be related to the imbalance of autophagy and apoptosis.